The therapeutic effect of bromocriptine in combination with spironolactone in patients with primary aldosteronism: a hypothesis generating pilot study - Wu, Vin-Cent (Oncotarget, 2017)
BACKGROUND: Dopamine D2-like receptors are attenuated in aldosterone producing adenoma, lead to overproduction of aldosterone in affected patients, and thus reported to serve as a potential treatment target for primary aldosteronism. The D2 dopamine receptor agonist bromocriptine has been used clinically for reducing tumor mass of pituitary adenomas of lactotroph origin. The aim of the present study was to assess the efficacy of adding bromocriptine to spironolactone in the biochemical control of primary aldosteronism. METHODS: Thirty patients (15 aldosterone producing adenoma) received bromocriptine treatment with dose titration to a daily dose of 7.5mg. Urine aldosterone and potassium excretion ratio of all patients were compared based on the result of metoclopramide test at baseline. RESULTS: On the basis of response to metoclopramide at baseline, the proportions of patients with lower urine aldosterone and urine potassium level after taking bromocriptine for six months were higher in the high metoclopramide response group. Initial aldosterone-renin ratio and high metoclopramide response at baseline were independent predictors of a decrease in aldosterone secretion after a six–month course of bromocriptine. The effects of bromocriptine added to spironolactone to reduce aldosterone secretion and potassium excretion in primary aldosteronism dissipated at 9 month after the initial treatment. CONCLUSIONS: In this pilot study, we found that short-term addition of bromocriptine to spironolactone improved the biochemical control of primary aldosteronism. Dopamine agonist is more effective in patients with high baseline aldosterone-renin ratio and those sensitive to metoclopramide stimulation. However, this effect dissipated after 9 months. CLINICAL TRIAL REGISTRY INFORMATION: ClinicalTrials. Gov number: NCT00451672; https://www.clinicaltrial.gov/ct2/show/NCT00451672?term=NCT00451672&rank =1; trial registry name: The Therapeutic Effect of Bromocriptin in Patients With Primary Aldosteronism.